Protopolybia Exigua (Hymenoptera: Vespidae) Nesting on Citrus Grandis (Rutaceae) - Brügger, Bruno Pandelo; Zanuncio, Antonio José Vinha; Wilcken, Carlos Frederico [UNESP]; Soares, Marcus Alvarenga; Zanuncio, José Cola (De Gruyter, 2019)
Social wasps are predators. Two nests of Protopolybia exigua (Saussure) (Hymenoptera: Vespidae) were collected on pomelo (Citrus grandis [L.]) (Rutaceae) leaves, 1 active and another abandoned. The colonies of P. exigua were located under pomelo leaves, providing protection against adverse environmental conditions. The active nest had 12 pedicels, 600 brood cells, and 15 adult wasps. The knowledge of nesting habits of wasps in agroecosystems favors the management of these insects for biological control.
Keywords: biological control; foraging; grapefruit